Pendekatan Nature Based Learning dalam Melatih Sikap Kemandirian Siswa di SMP Alam Insan Mulia Lubuklinggau - Muhammad Gunawan B; Khozin Khozin; Rahmad Hakim (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This study aims to describe the use of the Nature Based Learning (NBL) Approach in training students' independence attitudes at Insan Mulia Nature Junior High School Lubuklinggau. This study uses a qualitative approach with a case study research type. The data analysis used is the Miles, Huberman and Saldana analysis model with steps, data collection, data condensation, data display and data conclusion. The results of this study indicate that the use of the NBL approach at Insan Mulia Nature Junior High School Lubuklinggau by using the surrounding nature as a learning medium and several relevant methods both in intra curricular, co-curricular and extracurricular learning activities is able to foster an attitude of independence in students, especially in terms of independence in worship and independence in learning.